Effectiveness of Dexamethasone as a Preventive for PONV (Post Operative Nausea and Vomiting) - Rachma Pramita, Andhina; Pandu Harijono; Peter Gunawan Tandean (Majalah Anestesia & Critical Care, 2023)
Postoperative nausea and vomiting (PONV) is the second most common side effect on general anesthesia. This can be classified as a complex problem that caused by patient factors, anesthesia technique and surgery factors. PONV is a physiological event that associated with various neurophysological in both central and peripheral nervous system. Dexamethasone reported can decreased PONV and with the combination of antiemetic. The instrument used in this study are data taken from journal / articles indexed at least 10 internationally, such as Scimago, Scopus, Thompson Reuters. The journals that were used related to the effectivness of dexamethasone in preventing PONV published from 2017 to 2022. This research is a descriptive study using the literature review method. Dexamethasone has shown to be effective in preventing PONV at the dose of 4 mg IV, 5 mg IV and 8 mg IV.Dexamethasone combined with other drugs especially antagonist 5 HT3 is known more effective rather than single dose of dexamethasone. The common side effect that usually occurs are dizzy, headache, and low urine output. Although dexamethasone were proven to decrease the incident of PONV, but there are other drugs option that can be more effective than dexamethasone such as group of drugs from antagonist 5 HT3.